Mapping and Estimating the Impact of Drought on Food Crop Farmers Using Remote Sensing in East Nusa Tenggara Province - Latifa, Afina; Primadani, Avelia Deavy; Fitriyyah, Nur Retno; Kartiasih, Fitri (CV The Journal Publishing, 2023)
East Nusa Tenggara (NTT) is an area with a dry climate with a rainfall capacity of less than 2,000 mm/year, which is around 72%, so it is classified as a drought-prone area. The characteristics of drought hazards are quite different from those of other disaster hazards because they do not appear suddenly but occur slowly and are easily overlooked. The impact will begin to be felt when agricultural production, for example, food crops, and meeting drinking needs, begins to decrease, leading to a loss of livelihood due to a lack of water supply. Data on drought, especially regarding the area of food crop farming and the number of farmers affected by drought, is still very rare. This study aims to map and classify districts and cities in NTT Province based on the level of drought, estimating the harvest area and production of the food crop agricultural sector affected by the drought and estimating the number of food crop farmers affected by the drought as detected by remote sensing data. This estimate uses the MOD13Q1 remote sensing approach by measuring the Vegetation Health Index (VHI) of land affected by drought. The results of the study show that the most significant impact of the drought occurred in Timur Tengah Selatan district, with the number of affected farmers amounting to 20231 people. The percentage of food crop farmers whose livelihoods have been affected by the drought is quite large in the districts of Malaka, Sumba Barat Daya, Sabu Raijua, Timor Tengah Selatan, and Sumba Barat.